Tingkat Pemahaman dan Praktik Literasi Keuangan Pada Kelompok UMKM di Desa Karangtalun Kras Kediri - Moch. Wahyu Widodo; Imam Mukhlis (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aims to find out how the financial literacy of MSMEs in Karangtalun Village, Kras subdistrict, Kediri Regency. The research approach used is qualitative descriptive. The types of data used are primary and secondary data. Data collection techniques are carried out by observation, interviews, documentation. The research results show that MSMEs in Karangtalun Village do not understand financial literacy well. Business management is carried out conventionally.